#### Answer

$y' = \dfrac{10xy-3x^2y^2-1}{2x^3y-5x^2}$

#### Work Step by Step

In order to derivate this function you have to apply implicit differentation method.
First, take the function to it's f(x)=0 form
$x^3y^2-5x^2y+x-1=0$
Then derivate the whole equation. Rember the put y' every time you derivate y
$3x^2y^2+2x^3yy'-10xy-5x^2y'+1=0$
*Note: Here you have to apply the product rule twice
Solve for y' and you have the answer
$y'(2x^3y-5x^2) =10xy-3x^2y^2-1$
$y' = \dfrac{10xy-3x^2y^2-1}{2x^3y-5x^2}$